Valorisation of Three Underutilised Native Australian Plants: Phenolic and Organic Acid Profiles and In Vitro Antimicrobial Activity - Maral Seididamyeh; Anh Dao Thi Phan; Dharini Sivakumar; Michael E. Netzel; Ram Mereddy; Yasmina Sultanbawa (Foods, 2023)
Tasmannia lanceolata, Diploglottis bracteata and Syzygium aqueum are understudied native Australian plants. This study aimed to characterise the non-anthocyanin phenolic and organic acid profiles of the aqueous extracts obtained from the leaves of T. lanceolata and fruits of D. bracteata and S. aqueum by UHPLC-Q-Orbitrap-MS/MS and UHPLC-TQ-MS/MS. A total of 39, 22, and 27 non-anthocyanin polyphenols were tentatively identified in T. lanceolata, D. bracteata, and S. aqueum extracts, respectively. Furthermore, sugars and ascorbic acid contents as well as in vitro antioxidant and antimicrobial activities of the extracts were determined. Response surface methodology was applied to achieve an extract blend with a strong inhibitory effect against Pseudomonas viridiflava, the main cause of soft rot in vegetables, Bacillus subtilis, Rhodotorula diobovata and Alternaria alternata. The identified compounds including organic acids (e.g., quinic, citric and malic acids) and polyphenols (e.g., catechin, procyanidins, and ellagitannins) might contribute to the observed antimicrobial activity. Furthermore, this study provides the most comprehensive phenolic profiles of these three underutilised native Australian plants to date.